DAUN PANDAN WANGI (Pandanus amarylifolius Roxb.,) TERHADAP AKTIVITAS ANTIOKSIDAN - Angraiyati, Dewi; Hamzah, Faizah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purposes of this study were to obtain the effect of drying time on antioxidant activity and to obtain the best quality herbal tea fragrant pandan leaves (Pandanus amarylifollius Roxb.,). This study used a completely randomized design with 5 treatments and 3 replications. The treatments used were herbal tea fragrant pandan leaves are P1 (drying 110 minutes), P2(drying 130 minutes), P3 (drying 150 minutes), P4 (drying 170 minutes) and P5 (drying 190 minutes). Data were analyzed statistically using ANOVA and DNMRT at 5% level. The results showed that the drying time significantly affected the moisture content, ash content, antioxidant activity and sensory assessment (descriptive and hedonic). The treatment chosen from the results of this research was the treatment P3(Drying 150 minutes). Treatment of P3 had a water content of 5,17%, ash content of 3,30% and antioxidant activity (IC50) ofÂ  5,68 ppm. Rate sensory descriptive and hedonic herbal tea fragrant pandan leaves treatment P3 had the colour of powdered tea that was green and the colour of brewed tea was a little green, the aroma of tea powder was scented fragrant pandan leaves and the aroma was brewed tea wasa little scented fragrant pandan leaves, taste steeping tea was a little astringent. The overall assessment of herbal tea steeping fragrant pandan leaves was slightly favored and tea powder was too slightly favored by the panelists.Â Keywords: herbal tea, pandan fragrance, antioxidant activity and drying time.